An Analysis of Traffic Accident of the Elderly - KISHINO, Keiichi; MYOJIN, Sho (INFRASTRUCTURE PLANNING REVIEW, 1997)
As the aging on the population in Japan goes on very quickly these day, the safety of the traffic for aged people becomes an important subject. Base on the value of the casualties in each trip-time, the traffic accident of aged person is investigated in this paper. It is found that the ratio of traffic accident in night or in pedestrian is specially high. It is thought to be not only for the reason of lacking the mobility for aged people or the visibility in night, but also the relation between the properties of the trip and the traffic accident. Based on the result, the necessity of forming a regional community is discussed in the paper.